PENGARUH STRUKTUR MODAL, LIKUIDITAS TERHADAP NILAI PERUSAHAAN SUB SEKTOR KONSTRUKSI DAN BANGUNAN DI BURSA EFEK INDONESIA - Abdul Kohar (Fakultas Ekonomi, Program Studi Akuntansi, 2019)
Company value is the perception of investors about a company that has managed to manage company resources that support the company's stock price. Company value determines by several factors such as capital structure and liquidity which are the independent variables used in this study. The purpose of this study describes the capital structure and liquidity of the value of the company in the construction and building sub sector companies listed on the Indonesia Stock Exchange for the period 2013-2017. The sample used in this study amounted to 7 companies. The results showed a significant capital structure on firm value. While liquidity does not affect the value of the company. The results of the research published together reveal the structure of capital and liquidity illustrates the significant value of the company.